2013
DOI: 10.1039/c2cs35350d
|View full text |Cite
|
Sign up to set email alerts
|

Frustrated crystallisation and hierarchical self-assembly behaviour of comb-like polymers

Abstract: Comb-like polymers with flexible side chains chemically pended onto a polymeric backbone afford some unusual properties due to their hierarchical structures, such as nanoscale confined crystallisation, phase transition and conformational variations, length scale effects, etc. Considerable attention has been paid to these featured polymers, regarding their importance in understanding the correlation between hierarchical structure and the assembled morphologies. In this review, we reviewed the recent research pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
112
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 221 publications
(296 reference statements)
0
112
0
Order By: Relevance
“…The phase change enthalpy of poly(mono ethylene glycol n-tetradecyl ether vinyl ethers) (89 J/g) was approximately equal to that of poly(hexadecyl acrylate) (86 J/g) [29]. In the DSC curves of PC14EnVEs (n = 1, 2), the single peak demonstrated that there was only one packing form for the side chains, which was the hexagonal structure [8,30,31]. In order to examine the reliability of phase change materials in the process of actual use, PC14E1VE (Mn = 2.3 × 10 −4 ) and PC14E2VE (Mn = 2.3 × 10 −4 ) were chose for a thermal cycling test.…”
Section: Thermal Behavior Of Poly(mono/diethylene Glycol N-tetradecylmentioning
confidence: 98%
“…The phase change enthalpy of poly(mono ethylene glycol n-tetradecyl ether vinyl ethers) (89 J/g) was approximately equal to that of poly(hexadecyl acrylate) (86 J/g) [29]. In the DSC curves of PC14EnVEs (n = 1, 2), the single peak demonstrated that there was only one packing form for the side chains, which was the hexagonal structure [8,30,31]. In order to examine the reliability of phase change materials in the process of actual use, PC14E1VE (Mn = 2.3 × 10 −4 ) and PC14E2VE (Mn = 2.3 × 10 −4 ) were chose for a thermal cycling test.…”
Section: Thermal Behavior Of Poly(mono/diethylene Glycol N-tetradecylmentioning
confidence: 98%
“…At present, the energy-saving units such as polyethylene glycol (PEG) [27,28,32], fatty acid [33][34][35][36][37][38][39][40] and the alkyl side groups, etc. have been used to prepare polymeric-based PCMs [41][42][43][44][45][46][47]. Zhang et al prepared a series of poly(vinyl alcohol)-g-PEG copolymers with different graft ratios [48].…”
Section: Introductionmentioning
confidence: 99%
“…26 In addition, Dubin Paul L. et al have deeply discussed the critical conditions for complex formation of mixed micelles between polyelectrolyte and oppositely charged mixed micelles, 27,28 polycation/anionic-nonionic mixed micelle systems, 29 and anionic/nonionic-polycation mixed micelle systems. [28][29]32,33 Moreover, it is convenient to investigate the structure and interaction between PPEG and PQAs without interference from external forces. And through controlling the PH, temperature, distribution density, the length scale, and the grafting degree of alkyl side chains along polymeric main chains, these micro/nano-structural materials have different properties.…”
Section: Introductionmentioning
confidence: 99%